A lovasturizmus tapasztalatai és főbb sajátosságai Sopron környékén. - Kánya Diána (2017)
The purpose of my final thesis is to present the experiences and main features of equestrian on the examples of riding schools around Sopron. The reason for the choice of theme was that my favorite hobby is riding, which I have been reliving for almost seven years. First, I review the concept of tourism and its major sectors, and then position equestrian in the system of tourism. For the introduction and deeper understanding of the topic, the chapter of the essay is on between the horses and people ancient relationship. In the next chapter, we can get an insight into the more familiar and distinctive activities of equestrian. The dissertation deals not only with equestrian in Hungary, but it is also chosed experiences, particularly the equestrian in Germany and its regional significance. During my professional practice and previous visits, I was able to gather experiences in riding schools around Sopron. This is an opportunity to compare the major features of different riding schools located around Sopron. With the help of a questionnaire I have revealed the opinion of guests. Compared to their advantages and disadvantages, we can get a picture of the situation of equestrian lovers around Sopron and, to a greater extent, the level of development of equestrian in Hungary. SWOT analysis made me more proactive in this research. The other location of my internship was the Hotel Szieszta in Sopron. There, I managed to conduct a questionnaire survey amount the guests and revied the opinions of people who can not be regarded as riders. By this I have gained knowledge, which is rare, since riding tourism is not exactly the most popular and popular pastime. Drawing on the actions to be taken, the paper could be a starting point for development, as it contains all the important aspects. The most important thing would be to introduce the knowledge of horses in the curriculum at kindergarten and school early in childhood. Equal training of professionals should be ensured in all regions. It is necessary to produce technical, educational films and brochures that will help the information reach all ages. By overcoming the seasonality, it would be important to build riding school in all riding clubs.